Institutional publication of e-books: towards a socially useful model - Saorín, Tomás (Anuario ThinkEPI, 2013)
This work presents trends and models for electronic publishing of nonfiction books, with emphasis on education resources. The context of institutional publishers (universities, cultural centres) is outlined, from the point of view of global online publishing strategies that try to improve productivity by combining technologies and open licenses, innovations in format, and content repurposing and reuse.
Keywords: Digital publishing; Institutional publishers; Electronic books; E-books; Open books.